Pengembangan Model Digital Tahsin Berdiferensiasi pada Program Ekstrakurikuler Keagamaan di Madrasah - Budi Budi; Syahrur Ramli; Lainah Lainah; Darul Ilmi; Yahdillah Fahmi (IAIN Batusangkar, 2024)
The purpose of this study is to develop a valid tahsin activity model using digital media and differentiated learning. Based on preliminary observation, there are three problems were identified, first, the challenge of implementing classroom management creates a need for differentiated learning. Second, achievement in tahsin that is not yet optimal requires a learning media that can be used repeatedly. Third, madrasas are working to develop the digitalization of extracurricular activities. This was a research and development using the R2D2 development model (Recursive, Reflective Design, and Development). The product of differentiated tahsin digital model was developed using tarteel application through play store. Data sources were observation, interview, validity and practicality sheets. The research setting was MTsN 7 Lima puluh Kota district. The population of this study was grade VII students in 2022/2023 academic year. The research was conducted from February 2023 until February 2024. Data analysis showed that the validity of language aspect was highly valid (0.79) and the validity of content aspect was highly valid (0.84).